Pengaruh Biaya Operasional terhadap Pendapatan pada Perum Damri Cabang Bandung - Novalia Partalenta Hutasoit; Bella Chandra Nurfaizah; Gunardi Gunardi (Universitas Batanghari Jambi, 2022)
The general purpose of this research is to test how operating costs affect revenue. To obtain these data, the Pearson correlation test is used to measure the linear relationship of two variables. The data analysis used is descriptive qualitative. Analysis and the types of data are secondary and primary data. This study shows that there is a very significant relationship between operating costs and income, according to the value of r table 0,609 > 0,997 which is greater than the value of r table in the company, therefore the correlation value > between operating cost and income variables. It was concluded that there were obtacles to operating costin 2019 and 2020, resulting in a decrease in revenue.